Impact of India's National Tobacco Control Programme on bidi and cigarette consumption: a difference-in-differences analysis. Issue 1 (15th December 2018) - Nazar, Gaurang P; Chang, Kiara C-M; Srivastava, Swati; Pearce, Neil; Karan, Anup; Millett, Christopher
Abstract : Background: Despite the importance of decreasing tobacco use to achieve mortality reduction targets of the Sustainable Development Goals in low-income and middle-income countries (LMICs), evaluations of tobacco control programmes in these settings are scarce. We assessed the impacts of India's National Tobacco Control Programme (NTCP), as implemented in 42 districts during 2007–2009, on household-reported consumption of bidis and cigarettes. Methods: Secondary analysis of cross-sectional data from nationally representative Household Consumer Expenditure Surveys (1999–2000; 2004–2005 and 2011–2012). Outcomes were: any bidi/cigarette consumption in the household and monthly consumption of bidi/cigarette sticks per person. A difference-in-differences two-part model was used to compare changes in bidi/cigarette consumption between NTCP intervention and control districts, adjusting for sociodemographic characteristics and time-based heterogeneity. Findings: There was an overall decline in household-reported bidi and cigarette consumption between 1999–2000 and 2011–2012. However, compared with control districts, NTCP districts had no significantly different reductions in the proportions of households reporting bidi (adjusted OR (AOR): 1.03, 95% CI: 0.84 to 1.28) or cigarette (AOR: 1.01 to 95% CI: 0.82 to 1.26) consumption, or for the monthly per person consumption of bidi (adjusted coefficient: 0.07, 95% CI: −0.13 to 0.28) or cigarette (adjusted coefficient: −0.002, 95% CI: −0.26 to 0.26) sticks among bidi/cigarette consuming households. Interpretation: Our findings indicate that early implementation of the NTCP may not have produced reductions in tobacco use reflecting generally poor performance against the Framework Convention for Tobacco Control objectives in India. This study highlights the importance of strengthening the implementation and enforcement of tobacco control policies in LMICs to achieve national and international child health and premature NCD mortality reduction targets.